Cognitive Stimulation In Older Adults With Dementia: What Is The Impact On Their Caregivers' Health? - Thaíssa Thayara Machado Pinto; Mariana Asmar Alencar; Paula Maria Machado Arantes; Luciana de Oliveira Assis (Brazilian Society of Geriatrics and Gerontology, 2024)
OBJECTIVES: To identify and evaluate the effect of cognitive stimulation (CS) interventions for older adults with dementia on caregivers' health. METHOD: This systematic literature review was conducted in accordance with Preferred Reporting Items for Systematic Review and Meta-analysis Protocols (PRISMA) guidelines. A search was performed by two independent researchers in May 2018, using Scientific Electronic Library Online (SciELO), Latin American and Caribbean Health Science Literature Database (LILACS), Physiotherapy Evidence Database (PEDro), PsycINFO, and PubMed databases. The terms used were "dementia" AND "cognitive stimulation" and their equivalents in Portuguese and Spanish. For inclusion, articles should have been experimental, published from January 2007 to April 2018, with CS delivered to older adults with dementia by a professional or by a caregiver, and outcome measured in the caregiver. Quality of selected studies was assessed using the PEDro scale. RESULTS: The sample consisted of 10 studies, and only two reported CS benefits to the health of caregivers of older adults with dementia. CONCLUSION: This study found no consistent evidence of actual benefits of CS in older adults with dementia to their caregivers' health.